Imaging CNS modulation of pain in humans. - Bingel, U; Tracey, I (2008)
Pain is a highly complex and subjective experience that is not linearly related to the nociceptive input. What is clear from anecdotal reports over the centuries and more recently from animal and human experimentation is that nociceptive information processing and consequent pain perception is subject to significant pro- and anti-nociceptive modulations. These modulations can be initiated reflexively or by contextual manipulations of the pain experience including cognitive and emotional factors. This provides a necessary survival function since it allows the pain experience to be altered according to the situation rather than having pain always dominate. The so-called descending pain modulatory network involving predominantly medial and frontal cortical areas, in combination with specific subcortical and brain stem nuclei appears to be one key system for the endogenous modulation of pain. Furthermore, recent findings from functional and anatomical neuroimaging support the notion that an altered interaction of pro- and anti-nociceptive mechanisms may contribute to the development or maintenance of chronic pain states. Research on the involved circuitry and implemented mechanisms is a major focus of contemporary neuroscientific research in the field of pain and should provide new insights to prevent and treat chronic pain states.